A structured and in–depth representation of the semantic content of elementary and complex events. (10th April 2015) - Zarri, Gian Piero
'Events' are understood here, following the standard philosophical acceptation and in agreement with a Davidsonian and neo–Davidsonian approach, as the explicit, 'narrative' accounts of (spatio–temporal constrained) behaviours, states, actions and mutual interactions that concern animate/inanimate, human/non–human, abstract/concrete etc. well–identified 'entities'. Within this 'explicit' and 'symbolic' framework, we describe then how to isolate and represent in a computer–suitable form 'elementary events' inside a stream of narrative information, how to connect together these elementary events to give rise to 'complex events' through, e.g., 'causal' or 'conditional' relationships and how to make use of these formal structures for querying and inference operations. In this context, we will make use of NKRL (the Narrative Knowledge Representation Language), a language/environment expressly specified and implemented for dealing with narratives and temporal information, as formal support for our line of reasoning.